1978
DOI: 10.1017/s0033583500002298
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy in biochemistry and biology

Abstract: Resonance Raman (RR) spectroscopy provides detailed information on the vibrational and electronic properties of biochemical and biological chromophores. The analysis of RR spectra, using for example model compounds or a group frequency approach, enables us to form an accurate structural picture of the chromophore in its natural biological site. Moreover, the insight gained into the electronic states of a biological chromophore can be crucial to our understanding of its function. Thus the RR technique represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 184 publications
(204 reference statements)
1
27
0
Order By: Relevance
“…The sharp and strong v1 (stretching mode of the C ¼ C bonds at B1515 cm À1 ), v2 (stretching mode of the C-C bonds at B1155 cm À1 ) and v3 (deformation of the methyl groups at B1003 cm À1 ) peaks can be unambiguously assigned to carotenoids (Rimai et al, 1973;Tracewell et al, 2001;Robert, 2009). The position of the v1 band varies according to the length of the conjugated C ¼ C bond chain (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009). The v2 band varies depending on the molecular conformation, and the v3 band is related to carotenoid methyl groups (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009).…”
Section: Cells Containing Carotenoids Display Strong Rr Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharp and strong v1 (stretching mode of the C ¼ C bonds at B1515 cm À1 ), v2 (stretching mode of the C-C bonds at B1155 cm À1 ) and v3 (deformation of the methyl groups at B1003 cm À1 ) peaks can be unambiguously assigned to carotenoids (Rimai et al, 1973;Tracewell et al, 2001;Robert, 2009). The position of the v1 band varies according to the length of the conjugated C ¼ C bond chain (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009). The v2 band varies depending on the molecular conformation, and the v3 band is related to carotenoid methyl groups (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009).…”
Section: Cells Containing Carotenoids Display Strong Rr Effectsmentioning
confidence: 99%
“…The position of the v1 band varies according to the length of the conjugated C ¼ C bond chain (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009). The v2 band varies depending on the molecular conformation, and the v3 band is related to carotenoid methyl groups (Rimai et al, 1973;Carey, 1978;Tracewell et al, 2001;Robert, 2009). The RR signals of carotenoids are so strong that with 532 nm laser excitation the SCRR spectra of carotenoid-containing microorganisms predominantly display the v1, v2 and v3 Raman bands, which in Figure 1 arise from the typical carotenoid b-carotene.…”
Section: Cells Containing Carotenoids Display Strong Rr Effectsmentioning
confidence: 99%
“…We have recently demonstrated that the combination of Raman spectroscopy and advanced statistics can potentially discriminate human and animal blood traces [13,14]. Raman scattering is a powerful qualitative and quantitative analytical method based on a process where incident monochromatic photons interact with a sample to produce scattered photons with an energy distribution characteristic of molecular structure [15][16][17]. In the modern era of digital light detectors providing hundreds and thousands of data points in every measured spectrum, statistical analysis becomes an especially powerful tool.…”
Section: Open Accessmentioning
confidence: 99%
“…Raman spectroscopy can be used to uniquely identify molecules and has a wide range of in vivo applications (2,8,9,22). In terms of HbO 2 Sat determination, this method has the advantage that the oxygenation information is related only to the specific interaction of the photons with the Hb molecules, generating a unique Raman spectrum (6,7,12,36,40,41).…”
mentioning
confidence: 99%